(untitled) (International journal of artificial intelligence, 2026)
The rapid development of digital technologies has significantly transformed the global agricultural sector, creating new opportunities for increasing productivity, improving resource efficiency, and ensuring food security. The integration of digital solutions such as artificial intelligence, Internet of Things (IoT), drones, precision farming systems, big data analytics, satellite monitoring, and blockchain technologies has become one of the most important factors in modern agricultural development. This article analyzes the efficiency of implementing digital technologies in agriculture and evaluates their economic, social, and environmental impacts. Particular attention is given to the experience of developed countries and the prospects for implementing advanced digital systems in developing economies.